TYPES AND CONTENTS OF HALLUCINATIONS IN SCHIZOPHRENIA - De Sousa, Avinash (Journal of Pakistan Psychiatric Society, 2007)
Objective : Hallucinations are one of the commonest symptoms seen in schizophrenia. This research aimed to study the types and content analysis of various hallucinations seen in patients with schizophrenia. Design: Cross sectional study. Place and duration of study: This study was conducted in a private psychiatric hospital in Mumbai from January 2002 to January 2007. Subjects and Methods: The nature and content of hallucinations in 559 patients with schizophrenia was analyzed. The ptients meeting DSM IV criteria for Schizophrenia were asked to complete a questionnaire which enquired the hallucinatory experience. The data was tabulated and the results presented. Results: The most common type of hallucinations were of auditory nature (69.23%) and amongst that a majority of patients heard voices of an unknown person (54.52%). Visual hallucinations were less common (8.59%) followed by the other types of hallucinations. Conclusion: The study was an exploratory study in a private care setting. Auditory hallucinations were the most frequent as is generally reported in literature. More than one third (37%) of those experiencing auditory hallucinations had first rank symptoms. Key words: Hallucinations, Schizophrenia.